Responses of EMS on growth and yield of French bean (Phaseolus vulgaris) - KUMAR, AJAY; DHILLON, T S (The Indian Journal of Agricultural Sciences, 2020)
An experiment was conducted during 2017-18, to find out the effect of EMS on growth and yield of French bean. The germination percentage in M1 generation decreased with the increased in concentration of EMS both in laboratory and field conditions. The varieties Arka Suvidha and Falguni produced several heat tolerant mutants during February and March, sown for days to flowering, number of pods per plant and seed yield per plant. The maximum numbers of mutants were observed in lower EMS concentration (0.15%) during February and March as compared to higher EMS concentration (0.25 and 0.35%), thus application of lower concentration of EMS has been recommended for crop improvement purposes in French bean through mutation breeding.